2018
DOI: 10.14202/vetworld.2018.1648-1655
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and economic loss of fasciolosis and dicrocoeliosis in Arak, Iran

Abstract: Aim:Fasciolosis and dicrocoeliosis are important parasitic diseases worldwide, causing significant financial losses due to decrease in production and viscera condemnation in animals. We performed the current research to assess the epidemiology of these infections and determine their significance from an economic perspective in Arak, Iran.Materials and Methods:In total, we evaluated 118,463 sheep, 207,652 goats, and 43,675 cattle through necropsic analysis at the slaughterhouses. The average weight of sheep, go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…It carries public health importance also and as per WHO (2006) estimates 2.4 million people were infected with Fasciola hepatica and a further 180 million were at risk of infection. Arbabi et al (2018), from Iran, reported that Fasciola spp. infection caused financial losses of 7160 and 6098.4 USD magnitudes during 2013-2016 in sheep and goat respectively.…”
Section: Trematodes Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It carries public health importance also and as per WHO (2006) estimates 2.4 million people were infected with Fasciola hepatica and a further 180 million were at risk of infection. Arbabi et al (2018), from Iran, reported that Fasciola spp. infection caused financial losses of 7160 and 6098.4 USD magnitudes during 2013-2016 in sheep and goat respectively.…”
Section: Trematodes Infectionsmentioning
confidence: 99%
“…However, being asymptomatic and masked by the presence of pathological effects of multiple parasitic infections in ruminants, dicrocoelosis remained little known and underestimated by researchers. Arbabi et al (2018) reported losses of USD 10880 and 9079.2 respectively in sheep and goats resulted from dicrocoelosis during 2013-2016 in Iran, mainly due to condemnation of damaged liver.…”
Section: Dicrocoelium Sppmentioning
confidence: 99%
“…In Arak, Iran, Arbabi et al . [22] indicated a prevalence of 0.77% in cattle, goats, and sheep. While in the Mitidja region of Algeria, a prevalence of 0.07% and 0.86% in cattle was recorded, corresponding, respectively, to flukes and eggs positive cases [12].…”
Section: Discussionmentioning
confidence: 99%
“…The results are comparable to those obtained by Arbabi et al . [22] who reported no significant association between dicrocoeliasis and the season of the year. However, other authors have reported results with a significant association between season and dicrocoeliasis in sheep, cattle, and goats in Western Iran (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the availability of information on the prevalence of fascioliasis in cattle in Malaysia and the risk factors for the disease is very limited and fragmented. Data on the status of ruminant fascioliasis in Iran, Egypt, Thailand and Vietnam can aid disease prevention, control and treatment (5)(6)(7)(8). As demonstrated in the literature, fascioliasis is an important veterinary disease, as it causes considerable economic losses in the livestock industry due to the costs of anti-helmintics, drenches, labour and liver condemnation in meat inspections (9).…”
Section: Introductionmentioning
confidence: 99%